Shadow IT and computer-mediated collaboration: developing a framework based on social presence theory - Mallmann, Gabriela Labres; Maçada, Antonio Carlos Gastaud (Revista de Administração da UFSM, 2019)
The use of unauthorized technologies in the workplace, called shadow IT (SIT), is increasing within organizations. Previous research identified that Shadow technologies are often collaborative systems used by employees to communicate and share content with colleagues, clients, or external partners. Therefore, we aim to develop a framework for the influence of shadow IT usage on computer-mediated collaboration based on Social Presence Theory. We conducted a literature review that resulted in a framework and the development of research propositions. The literature suggests that there is a positive influence of shadow IT usage on employee collaboration and communications. This paper presents theoretical and practical contributions. Analyzing shadow IT and collaboration through a theoretical lens makes progress on the discussion about the consequences of these unauthorized technologies for individuals and organizations. It is important for organizations to comprehend these impacts, such as on collaboration, which, in turn, can facilitate improvements in employee productivity.